Overview of mitral regurgitation in Europe: results from the European Registry of mitral regurgitation (EuMiClip). (23rd February 2018) - Monteagudo Ruiz, Juan Manuel; Galderisi, Maurizio; Buonauro, Agostino; Badano, Luigi; Aruta, Patrizia; Swaans, Martin J; Sanchis, Laura; Saraste, Antti; Monaghan, Mark; Theodoropoulos, Konstantinos C; Papitsas, Michael; Liel-Cohen, Noah; et al.
Abstract: Aims: To determine the prevalence of mitral regurgitation (MR) in a large cohort of consecutive patients undergoing clinically indicated echocardiography and to examine the distribution of primary and secondary MR. Methods and results: All patients undergoing an echocardiographic study in 19 European centres within a 3-month period were prospectively included. MR assessment was performed as recommended by the European Association of Cardiovascular Imaging (EACVI). MR was classified according to mechanism as primary or secondary and aetiologies were reported. A total of 63 463 consecutive echocardiographic studies were reviewed. Any degree of MR was described in 15 501 patients. Concomitant valve disease of at least moderate grade was present in 28.5% of patients, being tricuspid regurgitation the most prevalent. In the subgroup of moderate and severe MR ( n = 3309), 55% of patients had primary MR and 30% secondary MR. Both mechanisms were described in 14% of the studies. According to Carpentier's classification, 26.7% of MR were classified as I, 19.9% of MR as II, 22.4% of MR as IIIa, and 31.1% of MR as IIIb. Conclusion: To date, this is the largest echocardiography-based study to analyse the prevalence and aetiology distribution of MR in Europe. The burden of secondary MR was higher than previously described, representing 30% of patients with significant MR. In our environment, degenerative disease is the most common aetiology of primary MR (60%), whereas ischaemic is the most common aetiology of secondary MR (51%). Up to 70% of patients with severe primary MR may have a Class I indication for surgery. However, the optimal therapeutic approach for secondary MR remains uncertain.